Spatial Variability of the Frontal Zones and its Eddies Generated in the Norwegian Sea - Travkin Vladimir Stanislavovich; Akhtyamova Avelina (Russian Journal of Earth Sciences)
The Norwegian Sea is the meeting place of warm and salty Atlantic waters with cold and fresh Arctic waters. The thermal and haline frontal zones (FZs) formed as a result of this interaction are areas of increased horizontal gradients of physical, chemical, and biological parameters, and have a significant impact on regional circulation. Many mesoscale eddies are generated in the FZs which are actively involved in the eddy dynamics of the Norwegian Sea. The aim of this work is to analyze the spatio-temporal variability of the vertical structure of FZs in the Norwegian Sea, as well as the eddies that form within their boundaries. The work uses data from the oceanic reanalysis GLORYS12V1, as well as the Atlas of Mesoscale Eddies “Mesoscale Eddy Trajectory Atlas product META 3.2 DT” for the period 1993–2021. We analyze the average depth and thickness of FZs, the vertical distribution of their thermohaline gradients and areas. The work examines the seasonal and interannual variability of the volumes of thermal and haline FZs, the seasonal and interannual variability of mesoscale eddies, their spatial distribution, trajectories, and main parameters. In some areas, deepening of FZs has been established, and their thickness can reach 900 m. The presence of significant haline gradients in the layer of 250–750 m has been found, while thermal FZs can be traced vertically up to 1000 m compared with haline FZs. In some FZs, the interannual variability may exceed the seasonal one. The greatest variability of haline FZs can be traced in the autumn period, and the smallest – in the winter–spring. It is noticeable in the summer period that thermal FZs weaken. Eddies can leave the boundaries of the FZs and move away from the place of origin for hundreds of kilometers. The number and lifetime of cyclones exceed similar estimates for anticyclones, while anticyclones travel long distances compared to cyclones.